1998
DOI: 10.1128/aac.42.3.624
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibilities of Penicillin- and Erythromycin-Susceptible and -Resistant Pneumococci to HMR 3647 (RU 66647), a New Ketolide, Compared with Susceptibilities to 17 Other Agents

Abstract: Susceptibility of 230 penicillin- and erythromycin-susceptible and -resistant pneumococci to HMR 3647 (RU 66647), a new ketolide, was tested by agar dilution, and results were compared with those of erythromycin, azithromycin, clarithromycin, roxithromycin, rokitamycin, clindamycin, pristinamycin, ciprofloxacin, sparfloxacin, trimethoprim-sulfamethoxazole, doxycycline, chloramphenicol, cefuroxime, ceftriaxone, imipenem, and vancomycin. HMR 3647 was very active against all strains tested, with MICs at which 90%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
3

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(59 citation statements)
references
References 25 publications
2
54
0
3
Order By: Relevance
“…Current treatment recommendations for CAP vary across countries, including either ␤-lactams at high dose, macrolides or new quinolones [1,[25][26][27]. However, macrolide resistance is increasing [28] and pneumococci resistant to fluoroquinolones are also starting to emerge, a development that appears to be a result of the selective pressure from increasing use of these agents [29,30].Telithromycin is active against erythromycin-resistant S. pneumoniae [16] and represents an alternative to fluoroquinolones in those situations in which they are prescribed as first-line therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current treatment recommendations for CAP vary across countries, including either ␤-lactams at high dose, macrolides or new quinolones [1,[25][26][27]. However, macrolide resistance is increasing [28] and pneumococci resistant to fluoroquinolones are also starting to emerge, a development that appears to be a result of the selective pressure from increasing use of these agents [29,30].Telithromycin is active against erythromycin-resistant S. pneumoniae [16] and represents an alternative to fluoroquinolones in those situations in which they are prescribed as first-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Telithromycin, the first member of a new family of antimicrobials -the ketolides -has been developed specifically to provide optimal therapy for the treatment of respiratory tract infections (RTIs) such as CAP [12].This agent is highly active against common, atypical and intracellular pathogens associated with CAP, including drug-resistant strains [13][14][15][16][17][18][19][20]. The pharmacokinetic profile of oral telithromycin supports a convenient once-daily dosage regimen, with drug concentrations in plasma and bronchopulmonary tissues and fluids consistently exceeding the MIC for common respiratory pathogens at a dose of 800 mg once daily [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…1. The ketolide compounds, with the 3-cladinose sugar substituted with a keto group, have recently shown promise as a third generation of novel and broadly effective antibiotics [8,16,17]. Replacement of the sugar with the ketone has generated a class of compounds that will not induce expression of the 23S rRNA methyltransferase activity leading to macrolide resistance [2,18].…”
mentioning
confidence: 99%
“…Previously conducted time-kill studies with telithromycin have demonstrated the agent's bactericidal activity against S. pneumoniae with a variety of phenotypic profiles, including resistance both to ␤-lactams and macrolides [3,4]. Moreover, these studies demonstrated that this activity was irrespective of the genotypic resistance profile (e.g.…”
Section: Discussionmentioning
confidence: 95%